Pengaruh terapi musik alam untuk menurunkan anxiety pada fase quarter life crisis bagi mahasiswa ners - Devita, Yeni; Juwita, Ratna; Nita, Yureya; Puswati, Desti; alfianur, alfianur; Oktaviani, Yoneta (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2025)
Background: Individual responses to developmental tasks and demands vary. Some individuals feel ready to face change, while others experience confusion and anxiety. This phenomenon is known as a quarter life crisis which describes a condition of uncertainty, hopelessness, and confusion in determining the direction of life, which is often experienced by university students. Stress, anxiety and loss of direction can have a negative impact on physical and psychological well-being, particularly in dealing with academic and social demands. Previous research shows that anxiety that arises during this phase can be reduced through non-pharmacological therapies, one of which is through nature music therapy. Purpose: To determine whether there is an effect of natural music therapy to reduce anxiety in the quarter life crisis phase for ners professional students. Method: A quantitative research with a quasi-experimental design with a pre-test and post-test nonequivalent control group approach. The number of respondents 68 consisted of 34 intervention groups and 34 control groups. The research used quarter life crisis and SAI instruments. Results: Age characteristics more than half of the respondents were 22 years old and for gender more than half were female. For the results of the average anxiety level of the intervention group 47.24 to 36.56 and the control group 44.56 to 40.97 for the statistical test results obtained p value 0.001 <0.005 then Ha is accepted and H0 is rejected. Conclusion based on the research results is that there is an effect of natural music therapy to reduce anxiety in the quarter life crisis phase for Ners Profession students. Keywords: Anxiety; College Students; Nature Music therapy; Quarter Life Crisis. Pendahuluan: Respon individu terhadap tugas perkembangan dan tuntutan berbeda-beda. Sebagian individu merasa siap menghadapi perubahan, sementara sebagian lainnya mengalami kebingungan dan kecemasan. Fenomena ini dikenal dengan istilah quarter life crisis yang menggambarkan kondisi ketidakpastian, keputusasaan, dan kebingungan dalam menentukan arah hidup, yang sering dialami oleh mahasiswa. Stres, kecemasan, dan kehilangan arah dapat berdampak negatif pada kesejahteraan fisik dan psikologis, khususnya dalam menghadapi tuntutan akademik dan sosial. Penelitian sebelumnya menunjukkan bahwa kecemasan yang muncul selama fase ini dapat diturunkan melalui terapi non-farmakologis, salah satunya melalui terapi musik alam. Tujuan: Untuk mengetahui apakah ada pengaruh terapi musik alam untuk menurunkan anxiety pada fase quarter life crisis bagi mahasiswa profesi ners. Metode: Jenis penelitian kuantitatif dengan desain quasi eksperimen dengan pendekatan pre-test and post-test nonequivalent control group. Jumlah responden 68 terdiri dari 34 kelompok intervensi dan 34 kelompok kontrol. Penelitian menggunakan instrumen quarter life crisis dan SAI. Hasil: Karakteristik usia lebih dari separuh responden berusia 22 tahun dan untuk jenis kelamin lebih dari separuh perempuan. Untuk hasil rata-rata tingkat anxiety kelompok intervensi 47.24 menjadi 36.56 dan kelompok kontrol 44.56 menjadi 40.97 untuk hasil uji statistik didapatkan nilai p value 0.001 < 0.005 maka Ha diterima dan H0 ditolak. Simpulan: Ada pengaruh terapi musik alam untuk menurunkan anxiety pada fase quarter life crisis bagi mahasiswa Profesi Ners. Kata Kunci: Anxiety; Mahasiswa; Quarter Life Crisis; Terapi Musik Alam